Conflicts and Harmonies in Land Use In The Kogyae Strict Nature Reserve - Awuku-Bor, M.S. (University of Ghana, 1999)
This study was carried out in the Kogyare Strict Nature Reserve, an area considered as ecologically fragile because of its strategic position between the northern savanna and the tropical rainforest in the South. The objective was to examine the conflict that has tended to affect the effective management of the reserve as a Strict Nature Reserve. This was looked at within the framework of socio-economic factors such as increasing population, claims of ownership and the general methods of land acquisition and the influence of these in explaining the incessant misuse of the reserve by inhabitants of the area. The impact of this misuse, expressed in the degradation of the vegetation was largely measured using the 1972/73 aerial photograph interpretation as a base year for the determination of change in land use and cover of the area using the 1991 Landsat T.M. image of the area. Wildlife was also made reference to. Three-hundred and sixty eight respondents were selected from seven communities, four of which had been affected by the eastward extension of the original Kujani Bush Forest Reserve in 1971. Opinion leaders, Odikros and Wildlife Department officials stationed in these communities were also interviewed for their opinions. The logistic regression model was employed to identify and explain the presence of the conflict on the basis of identified proximate variables. The incidence of conflict was accounted for mostly by claims of ownership over the area covered by 1971 eastward extension of the reserve and its resultant difficulty in getting land for farming. Connected with this is the loss of title to non-timber forest products (NTFP’S) such as wildlife even though these resources are extensively exploited illegally. Also, it was observed that ignorance of the laws governing the reserve was not a major factor in explaining the misuse of the reserve resources. Rather, this was dictated by the dire need for survival in the face of difficulties associated with life in most deprived rural areas. The study revealed an extensive destruction of the reminder of the forest reserve. It also recommends the encouragement of reafforestation programmes in the area, improvement in Community-Wildlife Department relations, increased budgetary allocation to the Wildlife Department and a co-ordination of activities of NGO’s working in the area with that of the Wildlife Department.
Thesis (MPhil)- University of Ghana